MEMENJOR TRADITION,THE CONTESTATION AND IMPLICATION TO HINDU’S COMMUNITY IN BALI - Ni Made Ary Widiastini (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2013)
The objective of this paper is to discuss the development of penjor in the post-modern and postindustrial era of society which tends for the contestation purpose. As a means of Hindu religious ceremony penjor has changed, exhibiting luxurious, extraordina ry, and magnificent conditions. Based on the survey in some areas of Bali (Denpasar regency, Badung regency, and Gianyar regency) it is found that extraordinary penjor is displayed during the Galungan Holiday. Extraordinary penjor is categorized into three types, namely (1) simple penjor, (2) penjor with symbols of mythologic animal, and (3) penjor with symbols of deities (gods and goddesses). Extraordinary penjor fulfills human desires. Following Adlin (2006:169), the capitalist cultural industry is rightful to take opportunity from the phenomenon in which the society appreciate the market religion (Atmadja, 2010: 73-89), i.e., in favor of buying extraordinary penjor as it is to hard to prepare it themselves.